MUTATION IN FRUIT PLANTS USING IONIZING RADIATION AND CREATION OF PROMISING VARIETIES - J.M. Ochildiyev (Bright Mind Publishing, 2025)
This article discusses the experiment of inducing mutations in seed and drupe plants using X-rays, the results and scientific news, the effect of different doses of radiation on growth, and the selected promising varieties.
Keywords: mutation, X-rays, fruit plants, breeding, plant genotype, pecan, date, pomegranate, apple, lemon.